Women on the screen: A comparison of gender representation in Indonesian cinema - Hasan, Yassar; Wulan, Roro Retno; Nurhayati, Iis Kurnia; Sintowoko, Dyah Ayu Wiwid (ProTVF, 2025)
Background: The emergence of Indonesian female directors is expected to be able to represent female characters in films based on the perspective of women themselves. However, in one film directed by a female director, a scene was found showing the female lead wearing revealing clothing that is identical to the concept of the male gaze. Purpose: This study aims to see whether the director's gender influences the depiction of female characters in the films they direct. Methods: Therefore, an analysis was conducted on four films directed by two male directors and two female directors to see how the representation of female characters in films is based on the director's gender using Sara Mills' critical discourse analysis. Results: Several contrasting differences were found between male and female directors in depicting female characters in films, especially in the four films analyzed, namely 27 Steps of May, Imperfect (by male directors), and Marlina si Pembunuh dalam Empat Babak, Yuni (by female directors), which can be seen in the aspects of characterization, location setting, explanations regarding the fate of predators, and a number of issues touched upon. Conclusion: Based on the comparative results, it was found that the director's gender influences the representation of women in films. Implications: Indonesian filmmakers, especially women, are expected to utilize the mass media of film to correct various stigmas and problems that tend to marginalize women in order to create a social and work environment that is free from gender-based discrimination.